Estudo de biocompatibilidade do titânio recoberto com nanofilmes de carbono e prata - Placias, Flavio Gomes [UNIFESP] (2018)
Introduction: The main barriers to new prosthetic materials are rejection and infection associated with the implant. Among the materials, titanium (Ti) substrate has been widely used due to its biocompatibility and mechanical properties. However, its biocompatibility and biointegration have been questioned in the literature. Objectives: The present study aimed to improve the biocompatibility and biointegration of Ti by coating its surface with carbon nanofilm Diamondlike Carbon (DLC) and to promote microbicide capacity with silver (Ag) nanoparticles. Methods: Coatings were performed with Plasma Technology. PlasmaEnhanced Chemical Vapor Deposition (PECVD) was the method used to apply the nanofilms coatings on Ti plates. The physical characterization of the plate surface was performed by Atomic Force Microscopy (AFM) and the microbicide capacity was analyzed by culture. The biocompatibility and biointegration were studied in rats (WistarEPM, n = 24) that received the implant of the plates in the abdominal wall. Animals were reoperated after 7, 28, 90 and 180 days. Tissue integration by AMF, histology and macroscopy were monitorized.Results: The AMF presented plates surfaces modifications after nanocoating. None of the coating groups demonstrated microbicide activity. The macroscopy showed tissue adhesion and no signs of rejection. This adhesion was confirmed by the AMF. The histology showed signs of chronic inflammation that did not prevent biointegration. Conclusions: The results showed that the nanocoating enabled the implanthost interaction, but did not alter the Ti biocompatibility. In addition, the Ag deposition, under the determinated conditions, did not demonstrated the expected antimicrobial effect.